ANALISIS NILAI-NILAI RELIGIUS PADA KARAKTER PAK HAJI DALAM SERIAL ADIT SOPO JARWO DAN RELEVANSI PADA PEMBELAJARAN AKHLAK DI MADRASAH IBTIDAIYAH - FITRIA NOVIKA, ERIZA (Jurnal Ilmiah Ibtida, 2025)
This study aims to analyze the religious values ​​displayed by the character of Pak Haji Udin in the animated film Adit Sopo Jarwo, determine the relevance of these values ​​in moral learning in elementary madrasahs, and develop effective and interesting teaching methods based on the character of Pak Haji Udin to improve students' understanding and appreciation of moral values. This study is a qualitative descriptive type. Qualitative descriptive method is a research approach used to describe and understand social phenomena or human behavior based on non-numerical data. Qualitative research emphasizes processes and meanings that are not measured strictly through statistics, but rather uses descriptive data such as written or spoken words from people and observed behavior. The animated film Adit and Sopo Jarwo has educational values ​​that are relevant to moral learning, especially among children. The character of Pak Haji Udin, with his wise and wise nature, conveys religious values ​​such as piety, tolerance, social concern, and sharing. These values ​​are reflected in various dialogues and situations in the series, which emphasize the importance of living in harmony, respecting each other, and helping others in a diverse society like Indonesia.